(untitled) (Bangladesh Journal of Medical Science, 2023)
Objective: Due to their prone to obesity and unbalanced nutrient intake this study was carried out to evaluate the daily energy and nutrient intake and obesity status of children and adolescents with attention deficit hyperactivity disorder (ADHD). Methods: The study was conducted on a total of 390 children (169 ADHD and 221 control groups) between the ages of 6-17 years. Body weight and height were measured and height-for-age-z-score (HAZ), weight-for-age-z-score (WAZ) and BMI-z-score (BMIZ) were calculated. 24-hour dietary recalls of the participants were recorded, and energy and nutrients intake were analysed. The ratio of meeting daily energy and nutrients adequacy according to age and gender was calculated. Results: The HAZ values of the children with a mean age of 10±2 years were within the normal range in most of both groups. The ratio of overweight-obese children was 43.8% in the ADHD group and 39.8% in the control group, respectively. The ratio of energy from fat was high in both groups (ADHD: 39%, control: 41%) (p <0.05). It was found that folic acid and thiamine were sufficient in both groups, pyridoxine was consumed in borderline excess, other vitamins were consumed in excess. All minerals except sodium were sufficient and sodium was consumed more. Folic acid and water consumption were found to be less in children with ADHD (p <0.05). Conclusion: Overweight and obese rates are common among children and adolescents with ADHD, and their eating habits are similar to those of their healthy peers. Bangladesh Journal of Medical Science Vol. 22 No. 01 January’23 Page : 171-179